2014
DOI: 10.1016/j.cplett.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of graphene from dry ice in flames and its application in supercapacitors

Abstract: We have synthesized graphene by reducing carbon dioxide in magnesium and calcium metal flames. The as-prepared graphene has been used as conductive additive to improve the electrical conduction of activated carbon-based supercapacitor electrodes. The graphene/activated carbon composite electrode showed an outstanding specific capacitance of 220 and 180 F g-1 at a current density of 0.1 A g-1 in 6 M KOH electrolyte when using graphene obtained in magnesium flames and calcium flames, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…In this method, the black product containing graphene and MgO was formed, and this product can be cleaned by using dilute HCl. Zhang et al also reported the synthesis of graphene by reducing CO 2 in magnesium and calcium flames and used the graphene formed for supercapacitor applications. Graphene was also produced in the author's laboratory by burning the Mg metal with Ni and Zn metal separately, in CO 2 (dry ice) …”
Section: Utilization Of Carbon Dioxide For Production Of Pc Cnts Anmentioning
confidence: 99%
“…In this method, the black product containing graphene and MgO was formed, and this product can be cleaned by using dilute HCl. Zhang et al also reported the synthesis of graphene by reducing CO 2 in magnesium and calcium flames and used the graphene formed for supercapacitor applications. Graphene was also produced in the author's laboratory by burning the Mg metal with Ni and Zn metal separately, in CO 2 (dry ice) …”
Section: Utilization Of Carbon Dioxide For Production Of Pc Cnts Anmentioning
confidence: 99%
“…The mechanism is discussed and the reactive progress is shown as Equation (1). Graphene can also be achieved by combustion of calcium (Ca) in the presence of CO 2 and the mechanism is shown in Equation (2) [86].…”
Section: Combustion Methodsmentioning
confidence: 99%
“…1,2 They are promising for di®erent potential applications in many technological¯elds such as sensors, nanoelectronics, actuators, nanocomposites, supercapacitors and photodetectors. [3][4][5] The fracture behaviors of graphene sheets play a signi¯cant role in designing graphene sheets-based nanostructures. In the recent years, there have been many studies on fracture characteristics of graphene sheets.…”
Section: Introductionmentioning
confidence: 99%